Kebijakan Pembelajaran Jarak Jauh pada Kondisi Khusus Covid-19 - Sri Indah Hardiyanti; Asih Ernawati (Arden Jaya Publisher, 2022)
This study aims to determine the dynamics of distance learning policies and the challenges faced by schools in implementing distance learning. This research uses qualitative research. This research was conducted at SD Negeri Karanglewas Kidul. Research data collection was carried out in September-November 2021 by interviewing school principals, class I-VI teachers, physical education teachers, and PAI teachers. Data collection was also carried out using data analysis techniques. The results of this study indicate that SD Negeri Karanglewas Kidul has adopted various policies made by the central government and local governments. The various policies implemented are aimed at supporting distance learning in education units. During distance learning, schools apply bold, engaging, or blended learning. The most dominant learning system used in bold learning is WhatsApp Group because this application is easily accessible to parents and makes it easier for teachers because it has complete features. Schools also apply offline learning and blended learning because during the implementation of distance learning there are obstacles or obstacles. Constraints or obstacles experienced such as teacher skills are not optimal in utilizing information technology, limited ownership of student gadgets, high internet quota needs and weak internet network connectivity, and students have difficulty understanding learning materials.